ФОРМУВАННЯ ЛІДЕРСЬКОЇ КОМПЕТЕНТНОСТІ ПІД ЧАС НАВЧАННЯ В ЗАКЛАДАХ ВИЩОЇ ОСВІТИ (World Science, 2016)
In the article the urgency of acquiring leadership competency by modern specialists of any branches is emphasized; the definitions of such concepts as "leader" and "competence" are analyzed, on the basis of which the generalization of the category "leadership competence" is made. The authors reveal the essence of leadership competence through its components, namely: knowledge, skills, responsibility. It the article the practical recommendations on the application of modern pedagogical technologies and teaching methods for higher education applicants in order to stimulate the formation of leadership competences during higher education institutions training are provided.